2006
DOI: 10.1124/jpet.106.113613
|View full text |Cite
|
Sign up to set email alerts
|

The Thyroid Disruptor 1,1,1-Trichloro-2,2-Bis(p-Chlorophenyl)-Ethane Appears to Be an Uncompetitive Inverse Agonist for the Thyrotropin Receptor

Abstract: In this study, we aimed at establishing whether two previously identified thyroid disruptors, the insecticide 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (DDT) and Aroclor 1254 (a complex mixture of polychlorinated water), may inhibit thyrotropin (TSH) receptor (TSHr) activity. DDT and Aroclor 1254 were shown to inhibit both the basal and bovine TSH (bTSH)-stimulated accumulation of cAMP in Chinese hamster ovary (CHO)-K1 cells stably transfected with the TSHr. Furthermore, both DDT and Aroclor 1254 did indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…More recently, we have analysed in detail whether this effect on thyroid homeostasis occurs via interaction with the TSHr. We have thus established that DDT inhibits both the basal and the TSH-stimulated accumulation of cAMP in Chinese hamster ovary CHO-K1 cells stably transfected with TSHr (Rossi et al 2007). Furthermore, DDT can still inhibit the basal TSHr activity, even when deprived of the extracellular domain, suggesting that DDT interacts directly with the transmembrane domain of the TSHr.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…More recently, we have analysed in detail whether this effect on thyroid homeostasis occurs via interaction with the TSHr. We have thus established that DDT inhibits both the basal and the TSH-stimulated accumulation of cAMP in Chinese hamster ovary CHO-K1 cells stably transfected with TSHr (Rossi et al 2007). Furthermore, DDT can still inhibit the basal TSHr activity, even when deprived of the extracellular domain, suggesting that DDT interacts directly with the transmembrane domain of the TSHr.…”
Section: Introductionmentioning
confidence: 95%
“…As controls, cells transfected with dopamine D1 and adenosine type A2a receptors have been shown to respond specifically to their respective agonists, even when stimulated in the presence of DDT. These observations have been interpreted as indicating that DDT acts specifically as an inverse agonist of the TSHr itself (Rossi et al 2007).…”
Section: Introductionmentioning
confidence: 96%
“…We studied in detail the mechanism by which DDT causes this effect and we demonstrated that DDT inhibits TSH receptor function by modifying the lipid organization of the cell membrane (De Gregorio et al 2011, Picchietti et al 2009, Rossi et al 2007). The fact that DDT is highly lipophilic might count for these inhibitory effects on the TSH receptor activity, inasmuch highly lipophilic molecules are known to deplete the cholesterol content in the cell membrane, which results in a defective organization of the raft microdomains that contain the TSH receptors (De Gregorio et al 2011).…”
Section: A New Property Of Ddt On Plasmamembranementioning
confidence: 99%
“…The literature available for DDT, due to its use as an insecticide worldwide, indicates around 10 μM the serum concentration of this compound in chronically exposed subjects (Chen et al 2005, De Jager et al 2006, and this is the concentration at which DDT begins to have an effect in our experimental setting (Rossi et al 2007). …”
Section: Potential Mechanism Of Neurotoxicity By Ddt Induced Extracelmentioning
confidence: 99%
See 1 more Smart Citation